2019
DOI: 10.7759/cureus.5404
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Propeller Protein-Associated Neurodegeneration (BPAN) Detected in a Child with Epileptic Spasms

Abstract: This report discusses a 13-year-old girl diagnosed with beta-propeller protein-associated neurodegeneration (BPAN). BPAN is an X-linked neurodegeneration disorder associated with a mutation in the WDR45 gene. It typically presents in childhood with encephalopathy, developmental delay, and seizures. Following an initial static phase, these symptoms then progress to dementia, dystonia, and parkinsonism in early adulthood. Our child initially presented with epileptic spasms, global developmental delay, speech del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Epilepsy, a feature most common in the first decade of life in BPAN patients, and dystonia, a feature typical of early adulthood, were instead not displayed by Wdr45 KO mice at any age. Hearing loss, likely confounded by the patients’ marked cognitive decline and therefore reported only in two BPAN cases (Rathore et al 2014 ; Kaleka et al 2019 ), was consistently observed in Wdr45 KO mice both from the progression cohort and phenotyping cohort, as revealed by the clickbox and ABR tests.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy, a feature most common in the first decade of life in BPAN patients, and dystonia, a feature typical of early adulthood, were instead not displayed by Wdr45 KO mice at any age. Hearing loss, likely confounded by the patients’ marked cognitive decline and therefore reported only in two BPAN cases (Rathore et al 2014 ; Kaleka et al 2019 ), was consistently observed in Wdr45 KO mice both from the progression cohort and phenotyping cohort, as revealed by the clickbox and ABR tests.…”
Section: Discussionmentioning
confidence: 99%
“…A spontaneous anatomical abnormality of the neocortex, focal cortical dysplasia type II (FCDII) is characterized by treatment-resistant epilepsy due to atypical neurons and dyslamination caused by deficient mTOR signaling [ 40 ]. Another severe mTORopathy, beta-propeller protein-associated neurodegeneration (BPAN), is associated with iron accumulation and neurodegeneration, presenting as intellectual disability, psychomotor retardation, febrile seizures, autism, progressive cognitive loss, dementia, dystonia and parkinsonism [ 41 ]. Polyhydramnios, megalencephaly and symptomatic epilepsy (PMSE), or Pretzel syndrome, is a rare brain disorder characterized by macrocephaly, craniofacial dysmorphism, infantile-onset treatment-resistant epilepsy and cognitive decline.…”
Section: Clinical Mtoropathiesmentioning
confidence: 99%